2004
DOI: 10.1242/dev.01345
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of chondrocyte differentiation and joint formation byα5β1 integrin in the developing appendicular skeleton

Abstract: The control point by which chondrocytes take the decision between the cartilage differentiation program or the joint formation program is unknown. Here, we have investigated the effect of α5β1 integrin inhibitors and bone morphogenetic protein (BMP) on joint formation. Blocking ofα5β1 integrin by specific antibodies or RGD peptide(arginine-glycine-aspartic acid) induced inhibition of pre-hypertrophic chondrocyte differentiation and ectopic joint formation between proliferating chondrocytes and hypertrophic cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 38 publications
6
79
0
1
Order By: Relevance
“…Several previous studies have indicated an inductive role of ␤1 integrins in hypertrophic differentiation. Signaling via ␣1␤1 and ␣5␤1 integrins was required for hypertrophy of cultured AC chondrocytes induced by transglutaminases (33,34), ␤1 integrin-blocking antibody impaired chondrocyte hypertrophy and collagen X deposition in sternal organ culture (35), and misexpression of ␣5␤1 integrin in embryonic chick legs resulted in joint fusion and initiation of the hypertrophic differentiation program (13). Finally, we have demonstrated that hypertrophic differentiation is delayed in ␤1 fl/fl -Prx1cre ؉ mice.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Several previous studies have indicated an inductive role of ␤1 integrins in hypertrophic differentiation. Signaling via ␣1␤1 and ␣5␤1 integrins was required for hypertrophy of cultured AC chondrocytes induced by transglutaminases (33,34), ␤1 integrin-blocking antibody impaired chondrocyte hypertrophy and collagen X deposition in sternal organ culture (35), and misexpression of ␣5␤1 integrin in embryonic chick legs resulted in joint fusion and initiation of the hypertrophic differentiation program (13). Finally, we have demonstrated that hypertrophic differentiation is delayed in ␤1 fl/fl -Prx1cre ؉ mice.…”
Section: Discussionmentioning
confidence: 68%
“…In the embryonic mouse limb culture system, administration of ␤1 and ␣5 blocking antibodies or RGD peptides induced ectopic joint formation between proliferating and hypertrophic chondrocytes of the growth plate, suggesting that ␣5␤1 integrin controls the decision between cartilage differentiation and joint formation during development (13). In adult joints, increased immunostaining of ␤1 integrin was reported in osteoarthritic monkey cartilage compared with normal cartilage (14) and in human OA samples at minimally damaged locations compared with areas with more severe lesions (15).…”
Section: -Col2a1crementioning
confidence: 99%
“…WNT, FGF, and Hedgehog signaling pathways network together in a variety of cellular processes, such as stem cell differentiation cascade, body axis formation, angiogenesis, organogenesis during embryogenesis, adult tissue regeneration during chronic persistent inflammation, cell fate determination and cancer cell proliferation during carcinogenesis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…FGF signals are transduced through FGF receptors and FRS2 docking protein to activate RAS-RAF-MAPKK-MAPK signaling cascade as well as PI3K-AKT signaling cascade (4,5,(22)(23)(24). Hedgehog signals are transduced through Patched receptors and Smoothened signal transducers to activate transcription of target genes, such as PTCH1, SFRP1, CCND2 and FOXM1 genes, based on active form of GLI family transcription factors (6)(7)(8)(9)(25)(26)(27)(28). WNT, FGF, and Hedgehog signaling pathways network together during embryogenesis, tissue regeneration, and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…WNT, Notch, FGF, Hedgehog, and BMP signaling pathways network together during embryogenesis, tissue regeneration, and carcinogenesis (1)(2)(3)(4)(5)(6)(7)(8). Canonical WNT signals are transduced through Frizzled receptors and LRP5/6 co-receptors to activate transcription of target genes, such as FGF18, FGF20, DKK1 and DKK4, based on the transcriptional complex consisting of TCF/LEF, ß-catenin, BCL9/BCL9L, and PYGO1/ PYGO2 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%